2006
DOI: 10.1016/j.neuroscience.2006.04.034
|View full text |Cite
|
Sign up to set email alerts
|

A vitamin A-free diet results in impairment of the rat hippocampal somatostatinergic system

Abstract: Abstract-Previous studies have revealed the presence of retinoid specific receptors in the hippocampus and have demonstrated that vitamin A deficiency produces a severe deficit in spatial learning and memory which are linked to a proper hippocampal functioning. It is also well known that the tetradecapeptide somatostatin binds to specific receptors in the hippocampus and, when injected into this brain area, facilitates the acquisition of spatial tasks. In addition, depletion of somatostatin by cysteamine impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The monitoring of serum and liver retinol concentrations in this study is important, considering that vitamin A is closely related to the function of the central nervous system, in the neurogenesis induction and neuronal patterning control (Shearer et al, 2012) and that the deficiency of this vitamin produces severe deficits in spatial learning and memory, which is associated with the correct functioning of the hippocampus (Hernández-Pinto et al, 2006) and consequently with the development of the reflex ontogeny in animals. In addition, vitamin A has defined function in the proper development of vertebrates (Gutierrez-Mazariegos et al, 2011), since its deficiency causes growth retardation in neonates (Samarut and Rochette-Egly, 2012), which reinforces its importance when it comes to irsomatic maturation.…”
Section: Parameters Groupsmentioning
confidence: 99%
“…The monitoring of serum and liver retinol concentrations in this study is important, considering that vitamin A is closely related to the function of the central nervous system, in the neurogenesis induction and neuronal patterning control (Shearer et al, 2012) and that the deficiency of this vitamin produces severe deficits in spatial learning and memory, which is associated with the correct functioning of the hippocampus (Hernández-Pinto et al, 2006) and consequently with the development of the reflex ontogeny in animals. In addition, vitamin A has defined function in the proper development of vertebrates (Gutierrez-Mazariegos et al, 2011), since its deficiency causes growth retardation in neonates (Samarut and Rochette-Egly, 2012), which reinforces its importance when it comes to irsomatic maturation.…”
Section: Parameters Groupsmentioning
confidence: 99%
“…Ten reviews were identified among the publications, 12 , 29 , 30 , 32 , 34 , 37 , 45 - 47 , 51 while 34 papers presented original data. 15 - 28 , 31 , 33 - 36 , 38 - 44 , 48 - 50 , 52 - 57 …”
Section: Resultsmentioning
confidence: 99%
“…VAD-mediated learning and spatial cognition deficits in rats may be facilitated by RA and RARs, according to some investigations ( Etchamendy et al, 2003b ). RA activates the RAR, a nuclear receptor that controls genes regulating the neuronal proliferation and differentiation, neurite outgrowth, synaptic plasticity, and other activities ( Hernández-Pinto et al, 2006 ; McCaffery et al, 2006 ). The downstream pathways in RA activation, however, are unknown.…”
Section: Retinoids In Potentiating Neuroplasticitymentioning
confidence: 99%